Pearson correlation and hyperparameter optimization for intrusion detection system / Fuad Mat Isa - Mat Isa, Fuad (2023)
Internet has become vulnerable place due to the rapid advancement of technology. The need of security approaches that will protect this sensitive information has never been more crucial. Intrusion detection system (IDS) is playing a pivotal role to provide an extra layer of security in the network. In order to effectively detecting network intrusion, one requires to gathering a large volume of data. This high dimension data needs to be synthesized and filter from redundant and irrelevant features to improve the performance of IDS. However, the existing technique unable to performed well in terms of accuracy, detection rate and false positive rate.